CompTIA Security + (Exam SY0-401) - Taylor, Pamela J.; Nufryk, Jason (Logical Operations, 2014)
CompTIA's Security+ is the #1 international vendor-neutral baseline security certification. In May 2014, CompTIA is releasing a thoroughly revised certification exam. CompTIA Security+ SY0-401 Exam Cram, Fourth Edition is a thoroughly updated guide to help prepare candidates for the new exam, using the proven Exam Cram method of study. It has been completely rewritten for the new SY0-401 exam objectives.